A fully integrated NPS PI model in R: An option for coupling nonpoint source models and GIS. (April 2020) - Su, Jingjun; Li, Xuyong
Abstract: The coupling of a geographic information system (GIS) and nonpoint source (NPS) models has significantly promoted NPS modeling and output visualization. This study reported an approach using R to fully integrate the GIS and a NPS Phosphorus indicator model, as well as to build an interactive web interface for the model". A case study in a semiarid northern China subwatershed showed that the proposed method was feasible, flexible and effective. Our experiences demonstrated that developing a fully-coupled GIS-NPS model system in R could simplify NPS modeling across computation platforms, promote modeling efficiency, implement dynamic simulations, enhance model inputs/outputs display and provide readily interactivity. We envision that the experiences could provide a promising option for NPS modeling. Highlights: Report a full integration of a non-point source Phosphorus indicator and the GIS in R. Full integration promoted modeling and visualization efficiency. R proves to be a promising option for non-point source pollution modeling.